MO505IMPACT OF THE COVID-19 PANDEMIC ON SYMPTOMS OF ANXIETY AND DEPRESSION AND HEALTH-RELATED QUALITY OF LIFE IN OLDER PATIENTS WITH CHRONIC KIDNEY DISEASE. (29th May 2021) - Voorend, Carlijn; Van Oevelen, Mathijs; Nieberg, Margot; Meuleman, Yvette; Franssen, Casper; Joosten, Hanneke; Berkhout-Byrne, Noeleen; Abrahams, Alferso C; Bos, Willem Jan W; Van Buren, Marjolijn
Abstract: Background and Aims: Older patients with advanced chronic kidney disease (CKD) are at increased risk for a severe course of the coronavirus disease-2019 (COVID-19) and vulnerable to mental health problems. We aimed to investigate prevalence and associated patient (demographic and clinical) characteristics of mental wellbeing (health-related quality of life [HRQoL] and symptoms of depression and anxiety) before and during the COVID-19 pandemic in older patients with advanced CKD. Method: An ongoing Dutch multicentre prospective cohort study enrols patients of ≥70 years with an eGFR <20 mL/min/1.73m 2 from October 2018 onward. With additional questionnaires during the pandemic (May-June 2020), disease-related concerns about COVID-19 and general anxiety symptoms were assessed cross-sectionally, and depressive symptoms, HRQoL, and emotional symptoms longitudinally. Results: The 82 included patients had a median age of 77.5 years (inter-quartile range 73.9-82.1), 77% was male and none had tested positive for COVID-19. Cross-sectionally, 67% of the patients reported to be more anxious for COVID-19 because of their kidney disease, and 43% of the patients stated that their quality of life was reduced due to the COVID-19 pandemic (Figure 1 ). Higher COVID-19-related stress was associated with a lower education level (p=0.036), and patients who reported to feel more down due to COVID-19 were more often female (p=0.020). Anxiety scores were higher among females compared to males (median 4.0 [IQR 3.0-9.0] versus 2.0 [0.0-6.0], p=0.020), and weakly associated to a decline in eGFR (correlation coefficient 0.197, p=0.023). Compared to pre-COVID-19, presence of depressive symptoms had increased (11% to 22%; p=0.022) and physical HRQoL declined (40.4±10.1 to 36.1±10.4, p<0.001). Mental HRQoL (50.3±9.6 to 50.4±9.9; p=0.913) and emotional symptoms remained similar. Males showed a greater decline in physical HRQoL (mean -5.3, SD 8.5) compared to females (mean -0.9, SD 5.7; p=0.039). Conclusion: Our findings show that older patients with advanced CKD suffered from disease-related anxiety for COVID-19, increased depressive symptoms, and reduced physical HRQOL during the COVID-19 pandemic. The impact of the pandemic on this vulnerable patient group extends beyond increased mortality risk, and awareness of mental health problems during the pandemic is essential. More in-depth investigation on disease-related COVID-19 concerns and its implications for the CKD population is needed.